PENGARUH VARIASI KONSENTRASI HPMC SEBAGAI GELLING AGENT TERHADAP SIFAT FISIK GEL ANTIJAMUR EKSTRAK LENGKUAS (Alpinia galanga (L.) Swartz) - Mikhania C.E., Agnis Pondinekaria Aditama, Sri Agita Ningrum (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2019)
The aim of this research was to know the influence of HPMC variation concentration as gelling agent againts physical properties antifungal extract galangal gel (Alpinia galanga (L) Swartz). Pre-experimental the one shot case study was used as the research design. Gel is formulated into three formulas with various concentration of HPMC 2% (F1), 3% (F2), and 4% (F3). The materials used in this research were galangal extract, propylenglycol, glycerin, methyl paraben, and aquadest. The result showed that the variation concentration of HPMC give influence to physical properties of organoleptic gel (form, smell and colour), viscosity, and spreadibility of gel but did not influence homogeneity and pH of the gel.Keywords: gel, galangal extract, HPMC